Application of the Integrative Business Experience ( IBE ) and Team Based Learning ( TBL ) at School of Business and Management ITB: Inception of Project - Lazo de La Vega, Patricia Salquero (SBM ITB, 2004)
The project of Integrative Business Experience (IBE) and Team Based Learning (TBL) will be implemented in School of Business and Management at Institut Teknologi Bandung (SBM-ITB). The implementation consist of three phases; Project Inception, Project Implementation and Project Outcome. The project inception is discussed in detail in order to disseminate the idea of IBE and TBL implementation. Workshop will be carried out to socialize and determine the IBE and TBL application at SBM-ITB.Â Keywords:Â Integrative Business Experience, Team Based Learning